If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 = 4m + -4 Reorder the terms: 8 = -4 + 4m Solving 8 = -4 + 4m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-4m' to each side of the equation. 8 + -4m = -4 + 4m + -4m Combine like terms: 4m + -4m = 0 8 + -4m = -4 + 0 8 + -4m = -4 Add '-8' to each side of the equation. 8 + -8 + -4m = -4 + -8 Combine like terms: 8 + -8 = 0 0 + -4m = -4 + -8 -4m = -4 + -8 Combine like terms: -4 + -8 = -12 -4m = -12 Divide each side by '-4'. m = 3 Simplifying m = 3
| 4+(-3/5)x=16 | | n/0.6=662/3 | | 2p^3+30p^2-68p= | | 86-2x=60 | | 3/2X5/8 | | v+v+v+v+v+10= | | (8x)+(11x-1)=180 | | x-0.7=8.52 | | 11/2*5/8 | | 6x-21=-12+9x | | P+7/4=37/8 | | 1.5x5/8 | | 0.22y-2.5=0.12y+1-0.6y | | 2y^3+3y^2-50y-75= | | x+x^2=2 | | (4y-8)/(3y)=6 | | 1/2/2 | | (-8c^2+4c+6)-(6c^2+7c-3)= | | -3n+7=-2 | | 9x^6-24x^4/3x^3 | | 8(2x+6)+13= | | 2(5x-31)+2x=72 | | 8/4+39/8=p | | (4y-8)/3y=6 | | 3x^2+2-16=0 | | 2(5x-31)(2w)=72 | | 2y^3+y^2-50y-75= | | -4x^2+(-7x)+(-4)+3x^2+8x+(-4)= | | -36x=3(6y-6) | | 4y-8/3y=6 | | 2(5x-31)+2x= | | X-8/4=7 |